Pembangunan dan Politik Pertanian di Indonesia - Sri Widodo (Caraka Tani: Journal of Sustainable Agriculture, 2007)
Agricultural sector get the especial priority in the effort economic development because this sector represent the dominant sector in Indonesia, either from contribution of national earnings, supply of employment, resource of stock-exchange etcetera. New approach in development ought to base on the fact that farmer have experienced of the process dinamisasi and modernize, so that farmer have more rational, have recognized the modern agriculture technology and recognize various high valuable agriculture commodity. Most of all farmer, including small businessman, have got the benefit from program of Bimas or green revolution, with adopting modern technology at paddy look like at growth rate high production until start a decay 1990-an. Food resilience do not only short-range, but long-range more important, that is how can create the situation able to push the stable production by trend mounting. This matter will concern some problem to determine the policy of concerning institute, produce, self sufficiency, stabilization of price and support price. Pprotection gets the efficiency, but protection needed a commodity which not yet ready to compete globally, to protect the emulation which do not fair, to protect the farmer, and to protect long-range food resilience.